OPTIMUM INSULATION THICKNESS FOR COLD STORAGE WALLS: CASE STUDY FOR TURKEY - Kurekci, N. Alpay (YILDIZ TECHNICAL UNIV, 2020)
Cold storage have heat gain resulting from walls, roof, lighting, human, cooled products, and infiltration. The biggest of these gains is the heat gain through the walls. In this study, the optimum insulation thickness which should be used on the walls of cold storage was calculated. Calculations were made for 5 cities of Turkey (Izmir, Istanbul, Ankara, Sivas, and Erzurum) with different degree-day values. Extruded polystyrene (XPS), Expanded polystyrene (EPS), glass wool, rock wool, polyurethane were chosen as insulants to be used on the walls. Cooling degree-day values of the selected cities were calculated by using the average external temperature of the cities and the cold storage temperature (4, 0, -5, -10, -15, -20, -25 and -30 degrees C). Calculations were repeated for different cold storage temperature values, and optimum insulation thicknesses that should be used for each temperature were found. In addition, energy savings and payback periods when optimum insulation thickness is used were also calculated.
Keywords: Cold Storage; Optimum Insulation Thickness; Energy Saving; Thermo-Economic Analysis; Mathematical Modeling; Thermal Insulation; ENVIRONMENTAL IMPACTS; BUILDING WALLS; ENERGY; Thermodynamics